Kajian Sebaran Dan Ketersediaan Ruang Terbuka Hijau (RTH) Di Kecamatan Tanah Grogot Kabupaten Paser - Muhammad Riduan; Arif Rahman Nugroho; Amalia Rezeki; Aswin Nur Saputra (Universitas Negeri Gorontalo, 2025)
This research is motivated by the increasing physical development and population growth in Tanah Grogot District, which has put pressure on the availability of Green Open Space (GOS). The literature review covers the concept of GOS, its ecological and social functions, spatial distribution patterns, and the application of Geographic Information Systems (GIS) for spatial analysis. The research uses a descriptive quantitative method supported by primary data through field observations, geotagging, and documentation, as well as secondary data from relevant government agencies. The analysis was conducted using on screen digitization and spatial processing using ArcGIS 10.4 to produce a GOS distribution map and calculate the ideal GOS requirement based on the standard of 20 m² per inhabitant. The research results show that there are 83 green open spaces (GOS) spread across Tanah Grogot District, dominated by private green spaces and cemeteries, with a major concentration in government centers and educational areas. The distribution of green open spaces is uneven, particularly in outlying residential areas. The total area of existing green open spaces is recorded at 380,895 m², while the ideal need is 1,658,980 m², resulting in a deficit of 1,278,085 m². These findings confirm that the availability of green open spaces remains far below the minimum standard and require strategies to increase the area, ensure equitable distribution, and strengthen the ecological and social functions of green open spaces.